Automated Adjustments of Inspired Fraction of Oxygen to Avoid Hypoxemia and Hyperoxemia in Neonates – A Systematic Review on Clinical Studies - Hummler, H.; Fuchs, H.; Schmid, M. (Klinische Pädiatrie, 2014)
Supplemental oxygen is commonly provided during transition of neonates immediately after birth. Whereas an initial FiO2 of 0.21 is now recommended to stabilize full-term infants in the delivery room, the best FiO2 to start resuscitation of the very low birth weight infant (VLBWI) immediately after delivery is currently not known. Recent recommendations include the use of pulse oximetry to titrate the use of supplemental oxygen. As reference values for pulse oximetry during the first minutes of life have become available, automated FiO2-adjustments are feasible and may be very useful for delivery room care to limit oxygen exposure. Beyond neonatal transition, preterm infants in the neonatal intensive care unit (NICU) commonly require supplemental oxygen to avoid hypoxemia, especially VLBWI receiving respiratory support because of poor respiratory drive and/or lung disease. For respiratory care of newborn infants in the NICU automated FiO2-adjustment systems have been developed and have been studied in preterm infants for limited time frames using short-term physiological outcomes. These studies could demonstrate short-term benefits such as more stable arterial oxygen saturation. Recent clinical trials have shown that oxygen targeting may significantly affect mortality and morbidity. Therefore, randomized controlled trials are needed to study the effects of automated FiO2-adjustment on long-term outcomes to prove possible benefits on survival, the rate of retinopathy of prematurity and on neuro-developmental outcome.
Keywords: hypoxemia; oxygen; oximetry; ventilators mechanical; closed-loop